Magneto-optical hyperthermia agents based on probiotic bacteria loaded with magnetic and gold nanoparticles. Issue 15 (29th March 2022) - Garcés, Víctor; González, Ana; Gálvez, Natividad; Delgado-López, José M.; Calvino, Jose J.; Trasobares, Susana; Fernández-Afonso, Yilian; Gutiérrez, Lucía; Dominguez-Vera, José M.
Abstract : Maghemite and prism gold nanoparticles were incorporated onto a probiotic bacterium to produce heterobimetallic systems with adequate features to act as dual agents in magnetic hyperthermia and photothermal therapy. Abstract : Probiotic bacteria were used as carriers of metallic nanoparticles to develop innovative oral agents for hyperthermia cancer therapy. Two synthetic strategies were used to produce the different therapeutic agents. First, the probiotic bacterium Lactobacillus fermentum was simultaneously loaded with magnetic (MNPs) and gold nanoparticles (AuNPs) of different morphologies to produce AuNP + MNP-bacteria systems with both types of nanoparticles arranged in the same layer of bacterial exopolysaccharides (EPS). In the second approach, the probiotic was first loaded with AuNP to form AuNP-bacteria and subsequently loaded with MNP–EPS to yield AuNP-bacteria–EPS–MNP with the MNP and AuNP arranged in two different EPS layers. This second strategy has never been reported and exploits the presence of EPS–EPS recognition which allows the layer-by-layer formation of structures on the bacteria external wall. The AuNP + MNP-bacteria and AuNP-bacteria–EPS–MNP samples were characterized by scanning (SEM) and transmission electron microscopy (TEM), and UV-vis spectroscopy. The potential of these two heterobimetallic systems as magnetic hyperthermia or photothermal therapy agents was assessed, validating their capacity to produce heat either during exposure to an alternating magnetic field or near-infrared laser light. The probiotic Lactobacillus fermentum has already been proposed as an oral drug carrier, able to overcome the stomach medium and deliver drugs to the intestines, and it is actually marketed as an oral supplement to reinforce the gut microbiota, thus, our results open the way for the development of novel therapeutic strategies using these new heterobimetallic AuNP/MNP-bacteria systems in the frame of gastric diseases, using them, for example, as oral agents for cancer treatment with magnetic hyperthermia and photothermal therapy.